PASAR RAKYAT KECAMATAN SUHAID - Fidrian, Rafi; Kalsum, Emilya; Caesariadi, Tri Wibowo (JMARS: Jurnal Mosaik Arsitektur, 2026)
Abstract Suhaid District currently lacks a well-organized and properly managed public market. Local residents primarily fulfill their daily needs through nearby small shops, while a temporary weekend market known as “Pasar Minggu Suhaid” operates only on Saturdays and Sundays. This market faces several issues, including the absence of a permanent building compliant with national standards, disorganized zoning between wet and dry stalls, and limited supporting facilities. Therefore, a planning and design proposal for the Suhaid District Public Market was developed based on the Type C Public Market standards as stipulated in the Ministry of Trade Regulation No. 21 of 2021. The design also integrates an arowana showroom to promote local potential and lodging facilities for traders and visitors from outside the area. The design process adopts a five-step method consisting of initiation, preparation, proposal, action, and evaluation. The final design comprises two main building masses: a commercial building and a public facilities/management building. The commercial building is vertically organized according to its functions—ground floor for parking and services, first floor for wet stalls, second floor for dry stalls and retail, and third floor for an arowana showroom and culinary area. Meanwhile, the public facilities and management building includes lodging on the second and third floors. This design aims to create a public market that meets national standards while enhancing local economic potential through the integration of cultural and economic functions centered on the arowana commodity.